The Phenomena Involved in the Thermal-dependent Tensile Mechanical Tests of Premium Rail Steel - João Vitor de Oliveira Cordeiro; Henrique Boschetti Pereira; Luiz Felipe Bauri; André Luis Hansen Vieira; Yuji Guilherme Iko Wasano; Arthur Helfstein Moura; Marcos Dorigão Manfrinato; Edwan Anderson Ariza Echeverri; Luiz Henrique Dias Alves; Giovani Gonçalves Ribamar; Hélio Goldenstein (Materials Research)
This study investigates the microstructural phenomena involved in the temperature-dependent mechanical properties of the Premium rail steel through tensile tests at various temperatures. Dilatometry and scanning electron microscopy were used to characterize the materials before and after tensile tests at different temperatures. Finite element simulations were carried out to measure the residual stresses based on the experimental data acquired from the previous tests. Results show that the total elongation increases with the temperature, except for the elongation at 500 °C. Microstructural analysis near the fracture region reveals a more pronounced pearlitic contour at this temperature, indicating a mechanical strength reduction process. The fracture surface exhibits brittle cleavage fracture at 100 °C, while ductile fracture is observed at temperatures above 400 °C. Additionally, spheroidized microstructure is found near the fracture surface at 600 °C, suggesting the influence of deformation on the spheroidization process. Furthermore, the microstructure away from the fracture shows spheroidization initiation at 700 °C, indicating that severe plastic deformation considerably reduces the partial austenitization temperature and its consequent cementite spheroidization. These findings provide valuable insights into the temperature-dependent behavior of Premium rail steel, which can aid in its effective use in high-temperature applications.